Anabaenolysins, Novel Cytolytic Lipopeptides from Benthic Anabaena Cyanobacteria - Jokela, Jouni (Public Library of Science, 2012)
Two novel cyclic lipopeptides, anabaenolysin A and anabaenolysin B, were isolated from two benthic cyanobacterial strains of the genus Anabaena. This novel class of cyanobacterial lipopeptides has a general structure of a small peptide ring consisting of four amino acids from which two are proteinogenic and two unusual; glycine(1), glycine(2), 2-(3-amino-5-oxytetrahydrofuran-2-yl)-2-hydroxyacetic acid(3) and a long unsaturated C(18) β-amino acid(4) with a conjugated triene structure. They are distinguished by the presence of a conjugated dienic structure in the C18 β-amino acid present in anabaenolysin A but not in anabaenolysin B. Conjugated triene structure generates a typical UV spectrum for anabaenolysins for easy recognition. Anabaenolysin A constituted up to 400 ppm of the cyanobacterial dry weight. We found evidence of thirteen variants of anabaenolysins in one cyanobacterial strain. This suggests that the anabaenolysins are an important class of secondary metabolites in benthic Anabaena cyanobacteria. Both anabaenolysin A and B had cytolytic activity on a number of mammalian cell lines.